Pengaruh Customer Value Dan Experiential Marketing Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pelanggan GO-JEK Mahasiswa Fakultas Ekonomi dan Bisnis UNISMA) - Ernawati Ernawati; Afi Rahmat Slamet; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and customer value and experiential marketing on customer loyalty with customer satisfaction on GO-JEK consumers in Malang Islamic Univesity students faculty of economics and business either partially or simultaneously. This reseach uses Explanatory Research with a quantitative apploach. The population in this study are consumers who come directly or indirectly at GO-JEK. Samples taken were 80 respondents. The sampling technique used was purposive sampling. Data wew anliyzed using multiple liner regression analiysis processed with SPPS 16.0 software. The data collection method used was a questionnaire. The result showed that customer value and experiential marketing partially significant effect on customer value loyalty through customer satisfaction. Keywords: Customer Value, Experiential Marketing, Customer Loyalty, and Customer Satisfaction.